Long-Run Investment Decisions, Operating Performance, and Shareholder Value Creation of Firms Adopting Compensation Plans Based on Economic Profits - Hogan, Chris E.; Lewis, Craig M. (Journal of Financial and Quantitative Analysis, 2005)
Abstract For firms that adopted economic profit plans between 1983 and 1996, we document changes in investment behavior that lead to improvements in operating performance and growth opportunities relative to these firms' past performance. The improvements, however, are similar to those realized by a set of non-adopting control firms that are selected on the basis of a logistic regression model of adoption choice. We then consider the possibility that some firms are better candidates for economic profit plans than others and classify adopters according to whether they make anticipated or surprising choices based on the adoption choice model. We find that anticipated adopters make changes in investment behavior that reduce invested capital and allow them to become more profitable than a sample of control firms that were expected to adopt but chose to continue using a traditional plan. A similar analysis of surprise adopters does not reveal significant performance differences relative to a sample of anticipated non-adopters. The classification analysis suggests that economic profit plans work best for firms that are expected to adopt such plans based on pre-adoption operating, organizational, financial, and compensation characteristics.